(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Acute heart failure is the primary reason for hospitalization among the elderly, leading to high mortality rates and healthcare expenses. In Vietnam, research on acute heart failure is limited, particularly in individuals aged 85 and older. Objective: Survey on characteristics and short-term prognosis of patients over 85 years old hospitalized with acute left heart failure Subject and method: Cross-sectional and longitudinal study. Results: The 145 patients had an average age of 88.5±3.5 years, with 33.8% being over 90 years old. The mean hospital stay was 8.3±1.3 days. Common underlying diseases in patients over 85 years old included hypertension with a high prevalence (76.6%), dyslipidemia (62.1%), chronic kidney disease (52.4%), vascular disease (45.5%), non-revascularized coronary artery (45.5%), chronic atrial fibrillation (39.6%), and type 2 diabetes (35.9%). The readmission rate within the initial 90 days was 32.4%, with patients with heart failure with reduced EF being 3.7 times more likely to be readmitted than those with preserved EF (OR=3.7, 95% CI: 1.732-8.037). The prescription rate of heart failure medications like ARNI and SGLT2 was restricted to <6.3% and the overall mortality rate in the study was 3.4%. Conclusion: The readmission rate within the initial 90 days for patients aged over 85. remained high, with the HFrEF patient cohort exhibiting a higher readmission rate compared to the HFpEF patient group.